EFIKASI DIRI DAN KEMATANGAN KARIR PADA SISWA SMA DAN SMK - Afifah, Meisa Zakiya; Purwantini, Lucky (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2017)
This study aims to determine the relationship between self efficacy with career maturity and differences in career maturity in high school and vocational students, as well as differences in career maturity in terms of future orientation. This research use quantitative method with research design using correlation and comparative research. Subjects in this study were students of class XII SMA and SMK Mandalahayu Bekasi amounted to 100 students consisting of 50 high school students and 50 students of SMK. This research uses self efficacy scale with reliability value of Alpha Cronbach 0,896 and career maturity scale with reliability value Aplha Cronbach 0,899. Data analysis techniques use Rank-Spearman correlation and Mann Whitney comparison. This study found that there is no relationship between self efficacy and career maturity. Based on test results Mann Whitney also known that there is no difference in career maturity between high school and vocational school students. However, there is a difference in career maturity when viewed from the future orientation. Students who have an orientation to work have a higher level of career maturity than students who have an orientation to continue their education